What Drives Conspicuous Consumption of the Modern-Day Consumers? A Study of Russian Luxury Car Owners. - Pominova, Natalia (2008)
Conspicuous consumption remains one of the most fascinating and one of the most under-researched areas of marketing. The most authoritative work on this matter remains "Theory of the Leisure Class" which was written by American economist, Veblen in 1899. Only recently, social sciences academics started to research this area again, however, many still call for more to be done. The present dissertation seeks to fill this gap by firstly improve general academic understanding of this phenomenon and secondly, empirically tests various explanations for conspicuousness in the context of scarcely researched Russian luxury car market, which is now the leading market for all the major luxury brands. The dissertation firstly, sets the scene by evaluating and criticising the relevant literature from 1899 till the present day. In total, twelve luxury cars owner were interviewed, offering a slightly different and perhaps unexpected view on conspicuousness. It was found that Veblenian type of conspicuousness was present, yet for the majority other qualities mattered more (safety, beauty, reliability); the impact of education, culture and gender however, produced inconclusive results; self-image affected on the other hand, significantly affected conspicuousness, making consumers more willing to buy luxury cars; and finally, reference group (friends and family) were found to have a varied impact, for the majority respondents themselves their opinions did not matter as such, close friends confessed that they evaluated and compared their friends' purchases with their own ones, but when it came to buying something, they never tried to buy the same goods. However, additional data obtained from one consumer indicated that amongst certain professions, or ages, reference group had a significant impact on purchasing decision, where complying with the 'trends' in use in that group was almost obligatory. In keeping with this study's methodological stance, an alternative model is also offered at the end of the dissertation, providing an alternative and more up-to-date theory of conspicuousness.